2019
DOI: 10.1097/mpg.0000000000002115
|View full text |Cite
|
Sign up to set email alerts
|

Recent Prescription Patterns for Children With Acute Infectious Diarrhea

Abstract: Antibiotics are over-prescribed for children with acute infectious diarrhea. Our investigation provides important information to promote education of physicians and of health policy considerations for appropriate antibiotic prescription practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…However, the appropriateness of the use could not be estimated, as the details of antibiotic prescription patterns were limited. Only a few studies have described antibiotic prescription patterns in Japan, and they are restricted to acute respiratory infections and gastroenteritis (Okubo et al, 2019;Yoshida et al, 2018). In addition, antibiotic prescription rates per population, frequently used as a measurement of antibiotic use in many countries (Dolk et al, 2018;King et al, 2019), have heretofore been unavailable in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…However, the appropriateness of the use could not be estimated, as the details of antibiotic prescription patterns were limited. Only a few studies have described antibiotic prescription patterns in Japan, and they are restricted to acute respiratory infections and gastroenteritis (Okubo et al, 2019;Yoshida et al, 2018). In addition, antibiotic prescription rates per population, frequently used as a measurement of antibiotic use in many countries (Dolk et al, 2018;King et al, 2019), have heretofore been unavailable in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of compelling evidences showing an effect in reducing the duration of diarrhoea of about 24 h and the risk of severe AID, several guidelines recommend the use of probiotics worldwide, and a large number of children currently receives probiotics for the treatment of AID [ 57 ]. A recent study in about 4500 Japanese children reported 46.7% of probiotic prescription during an AID episode [ 58 ]. The ESPGHAN is currently updating the official recommendations for the use of selected probiotic strains in children with AID [ 54 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…35 These findings were consistent with those of our previous studies with respect to overuse and physician preference of broad-spectrum antibiotics in common pediatric infectious diseases. [36][37][38][39] The discontinuation of ineffective, inappropriate, or potentially harmful treatment may be necessary for sustainable medicine. A previous study in the United States based on a large database reported that 60% of adults hospitalized with asthma received antibiotics in the absence of an indication for antibiotics with a wide variation in antibiotic treatment patterns in adults.…”
Section: Discussionmentioning
confidence: 99%